2006
DOI: 10.2337/diacare.29.03.06.dc05-1961
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Calcium Intake in Relation to Type 2 Diabetes in Women

Abstract: OBJECTIVE -The purpose of this study was to prospectively examine the association between vitamin D and calcium intake and risk of type 2 diabetes.RESEARCH DESIGN AND METHODS -In the Nurses' Health Study, we followed 83,779 women who had no history of diabetes, cardiovascular disease, or cancer at baseline for the development of type 2 diabetes. Vitamin D and calcium intake from diet and supplements was assessed every 2-4 years. During 20 years of follow-up, we documented 4,843 incident cases of type 2 diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
504
6
25

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 699 publications
(559 citation statements)
references
References 33 publications
24
504
6
25
Order By: Relevance
“…Thus, our data do not support an independent association between dietary intake of calcium and insulin sensitivity. These findings conflict somewhat with previous studies in women, where dietary and supplemental calcium intake was associated with a lower risk of type 2 diabetes [14] and the metabolic syndrome [25]. It should be noted that in those studies insulin sensitivity was not assessed.…”
Section: Comparison With the Literaturecontrasting
confidence: 86%
See 1 more Smart Citation
“…Thus, our data do not support an independent association between dietary intake of calcium and insulin sensitivity. These findings conflict somewhat with previous studies in women, where dietary and supplemental calcium intake was associated with a lower risk of type 2 diabetes [14] and the metabolic syndrome [25]. It should be noted that in those studies insulin sensitivity was not assessed.…”
Section: Comparison With the Literaturecontrasting
confidence: 86%
“…To answer these questions, we investigated the relationships between the serum levels of calcium and insulin sensitivity, evaluated using the hyperinsulinaemic-euglycaemic clamp, and secretion, evaluated as the early insulin response (EIR) during an OGTT, in a population-based cohort of elderly men with emphasis on subgroup analyses in individuals with normal fasting glucose, normal glucose tolerance and normal serum calcium. As a secondary aim, we also investigated the association between dietary intake of calcium and insulin sensitivity and secretion, as previous studies have suggested that higher dietary intake of calcium is associated with a lower risk of developing diabetes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Low vitamin D levels are common in patients with type 2 diabetes [1], over 50% of whom have a serum 25 hydroxyvitamin D (25OHD) level of <50 nmol/l [2,3]. Low vitamin D levels are associated with a higher risk of developing type 2 diabetes [4], worse glycaemic control in type 2 diabetes, higher serum lipid levels and a higher prevalence of cardiovascular disease [3]. Low vitamin D levels are also associated with an increased risk of hypertension and cardiovascular events in population-based studies [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Several clinical studies have evaluated the role of low 25OHD3 in the pathogenesis of T2DM, but with controversial results. [10][11][12][13][14][15] Recently, a study has looked into prediabetes and 25OHD3 in a representative population in the United States. This study reported that low serum 25OHD3 levels were associated with prediabetes in that population, with a strong correlation when vitamin D levels were lower than 17 ng/ml.…”
Section: Introductionmentioning
confidence: 99%